Adsorption of malic acid in aqueous solution by amberlite xad-4 - Sani, Nor Diyana Md (Universiti Sains Malaysia, 2009)
The adsorption of malic acid onto XAD-4 was studied. The effect of shaking time, pH, temperature, concentration of malic acid and amount of adsorbent on the adsorption of malic acid was investigated by batch process. It was found that the adsorption process works best at lower pH (pH 2.0) and shaking time of 75 min. The equilibrium data could be described well by Langmuir and Freundlich isotherms but the best fit is the Freundlich model based on the higher correlation coefficient (R2 ) value. Thermodynamic parameters such as enthalpy change (l1H 0 ), free energy change (l1Go) and entropy change (l1So) were calculated. The results shows that the adsorption is endothermic, spontaneous and entropy driven respectively.